Społeczeństwo posttotalitarne wobec zasad i wartości demokratycznych. Perspektywa filozoficzna (Politeja, 2022)
POST-TOTALITARIAN SOCIETY TOWARDS DEMOCRATIC PRINCIPLES AND VALUES: A PHILOSOPHICAL PERSPECTIVEMore years have passed since the last totalitarian bastion in Europe, the Communist system, collapsed. Apart from the fact that in the last phase of its existence, it was no longer as strong and did not exert as much influence on social life as before, citizens still expect there to be a strong state which is responsible for all aspects of life. In contrast to totalitarianisms, the democratic system is based on individual freedom and responsibility for oneself and others. This article addresses the issue of the existence of principles and values in societies that have experienced totalitarian rule and that currently have serious problems with building social relations on the basis of democratic principles. The systemic transformation from totalitarianism to democracy appears much faster in the political or even economic dimension than in the ethical and axiological one. Therefore, the author initially presents the mechanism of totalitarianism, referring to Hannah Arendt, Zbigniew Brzeziński, Antoni Kępiński or Józef Tischner, in order to later present the causes of disturbances in the formation of positive values in the post-totalitarian society. The anthropological and ethical conception adopted plays a crucial role here.